(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Sickle cell anemia is one of the most pressing diseases in the field of hemato-oncology, affecting millions of people worldwide. This hereditary disease, caused by a mutation in the gene responsible for the synthesis of beta-globin, leads to a change in the shape of red blood cells, which in turn causes their abnormal aggregation, impeding blood circulation and reducing the level of oxygen in the tissues. The relevance of the problem lies not only in the high prevalence of the disease, but also in the complexity of its diagnosis and treatment. This hereditary disease, caused by a mutation in the gene responsible for the synthesis of beta-globin, leads to a change in the shape of red blood cells, which in turn causes their abnormal aggregation, impeding blood circulation and reducing the level of oxygen in the tissues. The relevance of the problem lies not only in the high prevalence of the disease, but also in the complexity of its diagnosis and treatment.